Pengaruh Budaya Organisasi, Work Life Balance dan Disiplin Kerja Terhadap Kinerja Karyawan Hotel D’shining - Nurdin, Nurhilda; Ramly, Mansyur; Mahmud, Amir (Universitas Pahlawan Tuanku Tambusai, 2024)
Abstract This study aims to determine the current employee performance of Hotel D'Shining in Barru Regency. The variables used in this study are Organizational Culture (X1), Work Life Balance (X2), Work Discipline (X3) and employee performance (Y). The sample in this study was 70 respondents. The type of research used in this study is quantitative research using primary data. While the analysis method used in this study is data validity test, data reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, simultaneous influence test (F test), partial influence test (t) and simultaneous determination test R2. The research results show that (1)Organizational culture has a significant positive influence on the performance of employees at Hotel D'Shining in Barru Regency. (2) Work Life Balance has a significant positive influence on the performance of employees at Hotel D'Shining in Barru Regency. (3) Work discipline has a significant positive influence on the performance of employees at Hotel D'Shining in Barru Regency. Keywords : Organizational Culture, Work Life Balance, Work Discipline, Employee Performance